Polar/apolar compounds induce leukemia cell differentiation by modulating cell-surface potential. - Arcangeli, A (1993)
The mechanism of action of polar/apolar inducers of cell differentiation, such as dimethyl sulfoxide and hexamethylene-bisacetamide, is still obscure. In this paper evidence is provided that their effects on murine erythroleukemia cells are modulated by various extracellular cations as a precise function of the cation effects on membrane surface potential. The interfacial effects of the inducers were directly measured on the charged electrode, showing that both dimethyl sulfoxide and hexamethylene-bisacetamide, at the effective concentrations for cell differentiation and within the physiological range of charge density, adsorb at the charged surface and produce a potential shift. A linear correlation was found between this shift and the inducer effects on cell differentiation. Besides offering a different interpretation of the mechanism of action of the inducers, these findings indicate that surface potential has a signaling function. They may also be relevant to cancer treatments based on tumor-cell commitment to terminal differentiation.